2022
DOI: 10.3390/ijerph19095320
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study about the Associations between Physical Activity Level, Self-Perceived Health Perception and Mental Health in Informal Caregivers of Elderly or People with Chronic Conditions in Spain

Abstract: Providing informal care for older people, or people with chronic conditions, is associated with poorer physical and mental health and reduced quality of life. This task, in many cases, often relies on the women in the immediate family. Physical activity (PA) is a tool to enhance caregivers’ physical and mental health and their quality of life. Thus, this study aimed to analyse the associations between the physical activity level (PAL), self-perceived health (SPH) and mental health (SM) and its factors (positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…Suggestions for the best amount and highest limit of physical activity to decrease anxiety symptoms have been proposed for the general population ( Kim et al, 2020 ), and both resistance and aerobic exercise have been shown to improve anxiety and psychological distress ( LeBouthillier & Asmundson, 2017 ). In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Suggestions for the best amount and highest limit of physical activity to decrease anxiety symptoms have been proposed for the general population ( Kim et al, 2020 ), and both resistance and aerobic exercise have been shown to improve anxiety and psychological distress ( LeBouthillier & Asmundson, 2017 ). In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the present findings, PA has been also reported to be inversely correlated with successful coping and self-esteem in adults with asthma ( Denche-Zamorano et al., 2022e ), the same was found for these two variables and also for stress in adults with depression ( Denche-Zamorano et al., 2022d ), in adults with cancerous tumours ( Franco-García et al, 2023 ) and in a population of informal caregivers ( Denche-Zamorano et al., 2022c ). Successful coping ability ( Craven et al, 2022 ; Dahlstrand et al, 2021 ; Denche-Zamorano et al., 2022d ; Denche-Zamorano et al., 2022e ), stress ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) and self-steem ( Denche-Zamorano et al., 2022c ; Denche-Zamorano et al., 2022d ) seem to be improved by performing PA, which supports the available research that suggests the potential of PA on the prevention of depression, anxiety and other mental disorders ( Harvey et al, 2010 ; Herring, Lindheimer & O’Connor, 2014 ; Ji et al, 2022 ; Kandola et al, 2018 ; Lautenschlager et al, 2004 ; Schuch et al, 2019 ; Stubbs et al, 2017 ; Wijndaele et al, 2007 ). Despite the correlations found among PAL and GHQ-12 items and dimensions, and the available research supporting that performing greater PA is associated with a better mental state, cause–effect relationships cannot be stablished between performing larger PA and a better state in the dimensions evaluated by GHQ-12, including mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Psycho-environmental stressors result in absenteeism, dissatisfaction, high turn-over, poor coping with colleagues, and can be measured with tools based on subjective perception of work and life quality and personal satisfaction, such as Life Satisfaction Index , Work Ability Index . Self-evaluation has resulted being a good predictor of future illness and work ability loss according to some authors (Denche-Zamorano et al 2022 ).…”
Section: Background and Objectivementioning
confidence: 98%
“…According to studies about the effectiveness of PA in caregivers, being physically active has been associated with improved QoL and decreasing depression, stress, and caregiver burden (Lambert et al, 2016; Loi et al, 2014). In a large-scale study of caregivers in Spain Denche-Zamorano et al (2022)found that, when the PA levels of caregivers, increased, especially to moderate and vigorous levels, their self-perceived health perception improved (Denche-Zamorano et al, 2022). The relationship between QoL and PA in our study supports this finding.…”
Section: Discussionmentioning
confidence: 99%